36.5k views
0 votes
This is my third time posting this bc i kept getting the wrong answer please help me

This is my third time posting this bc i kept getting the wrong answer please help-example-1

2 Answers

3 votes

Answer:

B

Explanation:

the answer is the letter b

User Webx
by
4.6k points
2 votes

Answer:

B

Explanation:

So we have:


\frac{x^{(2)/(3)}}{y^{(-3)/(4)}}

First, we recall that we can switch an exponent from the denominator to the numerator if we multiply the exponent by -1 and vice versa. Therefore:


=x^{(2)/(3)}}\cdot {y^{(3)/(4)}

Now, use the following property:


a^(x/n)=\sqrt[n]{a^x}

Therefore:


x^{(2)/(3)}=\sqrt[3]{x^2}

And:


y^{(3)/(4)}=\sqrt[4]{y^3}

And so together:


=x^{(2)/(3)}}\cdot {y^{(3)/(4)}\\=\sqrt[3]{x^2}\cdot\sqrt[4]{y^3}

Our answer is B :)

User Simone Porcu
by
4.6k points